Анализ колебательно-вращательного спектра полосы N7 молекулы C2D4 - Фомченко А. Л. Анна Леонидовна; Чжан Фанцэ; Литвиновская А. Г. Анастасия Георгиевна; Замотаева В. А. Валерия Александровна; Кривчикова Ю. В. Юлия Валерьевна (Физико-математические науки, 2015)
Заглавие с экрана